Efectos de la migración en la producción nacional de Ecuador periodo 1991-2022, mediante modelos de series de tiempo - Cabrera Cabrera, Lizeth Yomara (2024)
Migration is the most recurrent means for Ecuadorians to respond to economic, political, environmental or social problems. Statistics indicate that by 2020, at least 1.2 million Ecuadorians will be living abroad. And during the last three years, Ecuador has received 871 thousand immigrants from different Latin American countries. Therefore, the general objective of this research is to analyze the relationship between migration and national production in Ecuador during 1991-2022, using statistical and econometric techniques that allow examining the short and long term relationship between the variables, with the purpose of proposing guidelines that contribute to reduce migration rates in the country. The data were obtained from World Bank [WB] (2023) and World Income Inequality Database [WIID] (2023) and were analyzed using an Autoregressive Vector Model and a Vector Error Correction Model, in addition to the application of a Granger causality test, considering the use of variables such as the migration index, production, technology and income inequality. The existence of a long- run equilibrium relationship between migration, production, technology and income inequality was determined: as well as a short-run equilibrium relationship between production and income inequality. In addition to the existence of a unidirectional causal relationship between production and migration, it was also found that there was a long-run equilibrium relationship between production and income inequality. In addition to the existence of a unidirectional causal relationship between production and migration. Finally, the main recommendation is the reduction of economic dependence on oil, as well as the implementation of comprehensive policies that include improvements in education, job training, access to health services, as well as the strengthening of public security.